1997
DOI: 10.1161/01.res.81.5.664
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Interleukin-1β and Monocyte Chemotactic and Activating Factor/Monocyte Chemoattractant Protein-1 in the Hypertrophied and Failing Heart With Pressure Overload

Abstract: Studies on the effects of proinflammatory cytokines on the heart suggest that they play some roles in the pathogenesis of congestive heart failure (CHF). To determine the involvement of proinflammatory cytokine in cardiac hypertrophy and CHF induced by mechanical overload, we investigated the expression of interleukin (IL)-1 beta and monocyte chemotactic and activating factor (MCAF)/monocyte chemoattractant protein-1 (MCP-1) in the left ventricle (LV) of Dahl salt-sensitive (DS) rats that showed hypertrophy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 44 publications
2
121
1
1
Order By: Relevance
“…23 An earlier report on MCP-1 expression in a hypertensive model of heart failure in the rat reported that MCP-1 expression was confined primarily to endothelial cells and infiltrating cells. 11 The discrepancy with our results may be due to the underlying cause of cardiomyopathy in the 2 different models.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…23 An earlier report on MCP-1 expression in a hypertensive model of heart failure in the rat reported that MCP-1 expression was confined primarily to endothelial cells and infiltrating cells. 11 The discrepancy with our results may be due to the underlying cause of cardiomyopathy in the 2 different models.…”
Section: Discussioncontrasting
confidence: 69%
“…10 Pressure overload-induced heart failure in hypertensive animals led to induction of MCP-1. 11 To date, the contribution of MCP-1 to the syndrome of heart failure is attributed solely to its potent chemoattractant properties on monocytes, the presence of which has been documented in cardiac specimens of heart failure. Interestingly, angiotensin II (Ang II), which plays a dominant role in the pathogenesis of CHF, also induces MCP-1 gene expression in vivo and in vitro.…”
mentioning
confidence: 99%
“…This class of receptors is present on the myocardium and vascular smooth muscle cell types and is capable of mediating important biological processes in a manner that is independent of inflammatory cells [34]. Recently, several studies have demonstrated that circulating chemokine levels, including that of CXCL12, are elevated in animals and humans with cardiac dysfunction [35][36][37]. Therefore, chemokines have been proposed as mediators of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study demonstrate that pioglitazone has inhibitory effects on the inflammatory reaction associated with MI/R injury and that pioglitazone decreases the extent of myocardial injury in a rat model. The important role played by MCP-1 in inflammatory and immune cardiovascular disorders has become increasingly apparent (Behr et al, 2000;Shioi et al, 1997). Recent studies from our laboratories have shown that plasma concentrations of MCP-1 are increased in the early phase of human acute myocardial infarction and that an antibody against MCP-1 reduces myocardial infarct size in rats subjected to MI/R (Ono et al, 1999).…”
Section: Discussionmentioning
confidence: 99%